Amenorrhea is a Current Pathological Condition in Gynecology - Temirova Dilnoza Olimzhonovna (American Journal of Bioscience and Clinical Integrity, 2025)
Amenorrhoea is the absence or abnormal cessation of the menstrual cycle. Functional hypothalamic amenorrhea (FHA), one of the most common and least studied forms of secondary (hypothalamic) amenorrhea, occurs due to a breakdown in the adaptation of the female body to the complex effects of psychosocial and metabolic stimuli. To date, there are no generally accepted methods for measuring the threshold value of potential stimuli and markers of the effectiveness of correcting this condition in women, and therefore the diagnosis, treatment and prevention of FGA are still empirical. The most promising direction in light of this problem is the development of multidirectional approaches to personalized management of patients with FGA, including correction of nutritional and psychoemotional status. Particular hopes are placed on the search for and application of omics (genomic, epigenomic, transcriptomic, proteomic and metabolomic markers of dysfunction of the hypothalamic-pituitary-gonadal axis in scientific and practical interests. This literature review shows the relationship between the occurrence of amenorrhea and stress, changes in diet and weight, excessive physical activity, as well as the COVID-19 pandemic. The literature search was conducted in Russian and English in the eLibrary, MEDLINE and Scopus, mainly for the last 5-10 years. Due to the insufficient study of the selected topic, sources dating back to the 1990s were also selected.